Chitosan’s effects on the acidity, copper ion release, deflection, and surface roughness of copper-nickel-titanium archwire - Ika Devi; Erliera Sufarnap; Finna; Eric Rionaldi P Pane (Dental Journal, 2023)
Background: Chitosan has an antimicrobial effect in oral hygiene control. Orthodontists sometimes prescribe mouthwash to adolescent patients. Copper-nickel-titanium (CuNiTi) orthodontic archwire is widely used in orthodontic treatment. Chitosan’s effects on the CuNiTi properties of orthodontic archwire are not generally known. Purpose: This study aimed to measure the acidity, copper ion release, deflection, and surface roughness of CuNiTi orthodontic archwire immersed in artificial saliva and 2% chitosan. Methods: This study comprised experimental laboratory research. Forty-two CuNiTi orthodontic archwires were divided into three groups. Group A consisted of 18 archwires immersed in artificial saliva, Group B consisted of 18 archwires immersed in 2% chitosan, and Group C was six archwires for the baseline sample. The two intervention groups (A and B) were divided into three subgroups of six samples and were subjected to different immersion times—i.e., two, four, and six weeks. Acidity, copper ion release, deflection, and surface roughness were measured using pH meters, atomic absorption spectrophotometry (AAS), a universal testing machine (UTM), and a scanning electron microscope (SEM). Results: The results showed that Group A was more alkaline than Group B, and it was significantly different only in Week 2. Group B’s copper ion release was significantly lower than Group A for all the time observations (p<0.05), and the deflection analysis showed no significant difference in any of the groups (p>0.05). Furthermore, the SEM images showed CuNiTi in Group A at Week-6 had the most porosities and defects. Conclusion: The chitosan produces buffer effects on the pH; it also exhibits lower copper ion release, no differences in unloading forces, and subjectively has better surface roughness.